Challenges Encountered on Bookkeeping Procedures in Finance Department at ABC College in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Effective bookkeeping procedures are essential for financial management and decision-making in any organization. This study aimed to identify the challenges encountered by thefinance department in bookkeeping procedures and propose recommendations to addressthese challenges.The study found that respondents encountered challenges related to recording and keepingrecords in the finance department but did not encounter significant challenges related toretrieving records. Respondents strongly agreed that bookkeeping is important in theirprocedures for recording documents, keeping records, and retrieving records. Mostrespondents preferred bookkeeping training and using bookkeeping software as a solution tothe challenges encountered.The researchers recommend implementing several measures to improve bookkeepingprocedures in the finance department at ABC College. These measures include providingtraining on best practices for data entry and investing in bookkeeping software with automaticupdates. To implement these recommendations, several proposed outputs include acomprehensive bookkeeping training program covering data entry best practices,bookkeeping skills, and bookkeeping software training. The finance department should alsoconsider implementing a backup generator or alternative power source to prevent data loss.Budgetary constraints should also be taken into account when deciding on the best course ofaction.
Keywords: Business